PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - Siregar, Rifka; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of corporate characteristics on corporate tax avoidance. The samples are 33 manufacturing companies which are listed in IDX and the sample collection technqiue has been done by using purposive sampling. The independent variables consist of profitability, leverage, size, capital intensity, and inventory intensity, the dependent variable in this research is tax evasion. The analysis technique employs multiple linear regressions analysis. The result of the research shows that leverage variable has significant influence on tax avoidance, a company which has high tax burden can carry out tax savings by increasing debt. Size has significant influence on corporate tax evasion practices, these companies encounter political power theory due to these companies have sufficient resources to take advantage of the political process which can benefit them and perform aggressive tax planning activities in order to obtain optimal tax savings. Variables i.e. profitability, capital intensity, and inventory intensity do not have any significant influence on corporate tax avoidance.Keywords: Characteristics of a company, Tax Avoidance, Political Power Theory